The Process Is Part of the Solution: Insights from the German Collaborative Project museum4punkt0. - Glinka, Katrin (Museum International, 2018)
The present article describes museum4punkt0, a three‐year project that develops and evaluates digital communication applications and technologies in museums. This project, held on a nationwide scale and funded by the Beauftragte der Bundesregierung für Kultur und Medien (Federal Government Commissioner for Culture and the Media, or BKM), aims to document and analyse the development process, encourages collaboration, and transfers workflows to the museum field that have their origin in disciplines such as design, Human‐Computer Interaction (HCI), or software development. I will first contextualise museum4punkt0, and then explain its overall structure, which includes an overview of the participating institutions and their specific use cases. This will be followed by a description of the ways in which collaboration, documentation, and reflection were devised to ensure that the project's main objectives are reached, in particular, the development and evaluation of innovative digital applications that can be reused in other institutions. Finally, I will discuss the (changing) role of digital technologies and research in museums, and highlight recent developments that bring the Humanities, communication technologies, computational methods, and adjacent fields together.